PERKEMBANGAN PENELITIAN PENGELOLAAN WAKAF: SEBUAH ANALISIS BIBLIOMETRIK - Luthfi Anwar Mahbubi; Didin Muhafidin; Nina Karlina (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
This study aims to understand the global publication’s trend on waqf management around the world until April 2022. This descriptive bibliometric study was conducted by utilizing a literature review from Scopus database. VOSviewer software is used to visualize the results. The analysis carried out includes publication trend, contributions based on country of origin, journals distribution, the most cited articles, bibliographic coupling analysis, and keyword analysis. The results showed that the number of publications on waqf management had increased since its inception in 2007 to April 2022. Malaysia is the country with the most researchers to produce 29 articles. The article entitled “Waqf Accounting and Management in Indonesian Waqf Institutions: The Cases of Two Waqf Foundations” from the journal Humanomics is the most cited with a total of 27 citations. Waqf, waqf management, and cash waqf are the top three most discussed keywords. The keywords "sustainable development", "muslim community", and "history" are not widely discussed. Thus, research on waqf management in the future can raise further issues related to sustainable development, Muslim communities, and history.Keywords: Bibliometrics, Scopus Database, VOSviewer, Waqf Management Kata Kunci: bibliometric; database scopus; pengelolaan wakaf; VOSviewer